Thermal lens microscope sensitivity enhancement using a passive Fabry–Perot-type optical cavity. (7th April 2016) - Cabrera, H; Cedeño, E; Grima, P; Marín, E; Calderón, A; Delgado, O
Abstract: We developed a thermal lens microscope equipped with a passive optical cavity, which provides an optical feedback for the multiple pass of the probe laser beam to enhance sensitivity. Considering the maximum absorption peak for Fe(II) at 532 nm wavelength, we have achieved a 6.6-fold decrease in the limit of detection (LOD) to a level of 0.077 μ g · l −1 without a cavity. The possibilities to use thermal lens detection combined with an optical resonator was proposed and a drastic thermal lens signal enhancement was achieved using very low excitation power. The corresponding LOD for Fe(II) was further decreased to the level of 0.006 μ g · l −1 which represents an 85-fold decrease of the LOD value. This setup is a promising device, which can be applied as a sensitive tool for detecting chemical traces in small volumes of solutions.